Pelatihan Pemanfaatan Media Sosial dalam Upaya Melakukan Branding bagi Sanggar Seni Sekar Pandan Cirebon - Yudha Pradhana; Adi Prakosa; Fadhly Akbar Rizkiansyah (Program Studi Manajemen FEB UNM, 2023)
The Sekar Pandan Art Studio is one of the studios that until now still maintains the authenticity of the Cirebon Mask Dance. However, the lack of understanding of the community, especially the management of the Sekar Pandan Art Studio towards social media, has made his name not too heard outside the Cirebon area. Through Community Service activities, it is hoped that it can contribute to the importance of branding and also the use of social media in terms of building branding. The purpose of this activity is to provide education to the public, especially the management of the Sekar Pandan Art Studio, how to utilize social media in terms of branding so that the name Sekar Pandan Art Studio can be heard at least outside the Cirebon area. In addition, this activity is expected to provide education about social media literacy. The results obtained from this Community Service include the managers of the Sekar Pandan Art Studio realizing that they are not maximizing social media in carrying out studio branding and a lack of understanding from managers in utilizing social media even though studio managers basically have social media accounts, including Youtube and Instagram. The conclusion of this Community Service is that the management of the Sekar Pandan Art Studio will maximize social media in carrying out branding so that the name of the Sekar Pandan Art Studio will be more heard than at present, both regionally, namely the Cirebon region and its surroundings, nationally and internationally.